Gambling, Risk, and Law: Exploring the changing roles of the individual and the state in a multi-faceted gambling regulation arena - Murray, Calum James (Kent Law Review, 2019)
This paper presents an examination of ways in which risk is deployed to govern the gambling market. Drawing on Michel Foucault’s concept of governmentality, it seeks to explore how the dominant socio-political discourse of neoliberalism as well as the perception of risk as a rationality and technology of government inform the ways in which the gambling industry and its associated risks are increasingly governed through the individual gambler, rather than through state-enforced mechanisms. Besides confirming Foucault’s observations that the practice of government occurs at numerous levels and is delegated to various (non-state) actors, the growing reliance on individuals as a form of governance in the gambling industry also showcases the gradually changing relationship between the individual and the state. A relationship once characterised by the omnipresence of a paternalistic and assertive state becomes a relationship of cooperation and mutual reliance for the purposes of promoting both governance efficiency in an increasingly diverse and complex gambling market as well as the welfare for individual gamblers.